THE TRADITIONAL USE AS A REGULATORY CATEGORY – EXPERIENCES IN EUROPE - Coquillette, E.; Peschel, W. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The new European legislation introduced with the Directive 2004/24/EC amending Directive 2001/83/EC a harmonised registration scheme for traditional Herbal Medicinal Products (HMPs) at multinational level. With this legislation the Traditional Use (TU) of HMPs gained a new meaning, because the proof of traditions may replace individual product data for efficacy and safety. With the pan-European upgrade from a simply historic category to a legal one, the TU is now part of the regulatory strategy for HMP manufacturers and as such unique in the licensing of pharmaceuticals. We compared the European legal basis for traditional HMPs with the former legal practice by some European countries (France, Germany, Hungary, Spain) and also non-European countries (Australia, Brazil, Canada, India) in terms of six major criteria: (I) self medication character, (II) specified strength and posology, (III) appropriate route of administration, (IV) period of traditional use, (V) sufficient data on safety, and (IV) plausibility of pharmacological effects. Examples (e.g. Equisetum, Solidago, Echinacea). For the acceptance of evidence for Community monographs, the adjustment with monographs of the European Pharmacopoeia, and experience from referral cases are presented. In addition, the different concepts of (1) well-established use medicinal products and (2) foodstuffs with health claims - the major borderlines within European legislation- are discussed. The experiences of European harmonisation process might be useful for Africa and other regions of more diverse traditions when accepting rationally TU in order to strengthen the position of HMPs on the market.